Stability analysis of doubly fed induction generator considering the effect of rotor current controller - Shawon, M.; Li, X.; Al-Durra, A.; Caruana, C.; Muyeen, S.M. (2012)
This paper discusses small signal stability analysis of grid connected wind turbine driven doubly fed induction generator (DFIG) system. It also presents effect of compensation of rotor back electromotive force (EMF) voltage as well as influence of rotor active damping resistance in rotor current controller under a three phase voltage dip. Since rotor back EMF has an important role in limiting rotor inrush current during voltage dip, compensation of this voltage helps to improve the fault ride through capability (FRT) of DFIG. Furthermore, it has been investigated that rotor current control closed loop bandwidth, rotor back EMF and rotor active damping have a great impact on stator modes as well as affecting the dynamic characteristics of DFIG. However, with the compensation of rotor back EMF and inclusion of rotor active damping it has been observed that the system stator mode deteriorates. Finally, the analysis is performed for different combinations of rotor back EMF compensation and rotor active damping using both time domain and modal analysis approaches.